The Routledge handbook on crime and international migration - Pickering, Sharon, 1972-; Ham, Julie (Milton Park, Abingdon, Oxon, UK : Routledge, 2015)
'The Routledge Handbook on Crime and International Migration is concerned with the various relationships between migration, crime and victimization that have informed a wide criminological scholarship often driven by some of the original lines of inquiry of the Chicago School. Historically, migration and crime came to be the device by which Criminology and cognate fields sought to tackle issues of race and ethnicity, often in highly problematic ways. However in the contemporary period this body of scholarship is inspiring scholars to produce significant evidence that speaks to some of the biggest public policy questions and debunks many dominant mythologies around the criminality of migrants. The Routledge Handbook on Crime and International Migration is also concerned with the theoretical, empirical and policy knots found in the relationship between regular and irregular migration, offending and victimization, the processes and impact of criminalization, and the changing role of criminal justice systems in the regulation and enforcement of international mobility and borders. The Handbook is focused on the migratory'fault lines' between the Global North and Global South, which have produced new or accelerated sites of state control, constructed irregular migration as a crime and security problem, and mobilized ideological and coercive powers usually reserved for criminal or military threats. Offering a strong international focus and comprehensive coverage of a wide range of border, criminal justice and migration-related issues, this book is an important contribution to criminology and migration studies and will be essential reading for academics, students and practitioners interested in this field'--
part I. Immigration and crime -- part II. Crime control, criminal justice and migration -- part III. The politics of migration, security and crime -- part IV. Migration, law and crime -- part V. Crimes of mobility -- part VI. Criminology and the border.
Includes bibliographic references (pages 392-395) and index.
Keywords: Crime; Emigration and immigration; Race